The Juridical Overview Of Customary Land Registration - Intan Haryanti; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2021)
Indonesia in Article 18 B paragraph 2 states that the State recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with community development and the principles of the Unitary State of the Republic of Indonesia, which are regulated by law. This study aims to 1). Describe the Land Registration Policy in the current era; 2). Describe the legal policy of ulayat land registration. This type of research is a doctrinal research with a juridical approach that uses secondary data as the main data source. The current land registration policy is based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL) which targets 126 million parcels of certified land throughout Indonesia by 2025. Policy on ulayat land registration Referring to PP No. 27 of 1999 concerning registration, it does not make ulayat land as land that can be issued a certificate, even though providing legal guarantees and protection for ulayat land is a mandate of the 1945 Constitution of the Republic of Indonesia and the UUPA. Therefore, the government can issue a Certificate of Customary Land through a Regional Regulation as the output of the Customary Land Registration.